Palliative rehabilitation interventions in palliative care: a scoping review protocol - Parola, Vitor Sérgio de Oliveira (2020)
Objective: The objective of this scoping review is to examine and map interventions of palliative rehabilitation that are implemented and evaluated in palliative care. Introduction: Palliative rehabilitation is defined as the process of helping an individual with a progressive, frequently advanced and/or incurable disease reach their physical, psychological, and social potential consistent with physiological and environmental limitations and life preferences. Therefore, it is essential to examine and map interventions of palliative rehabilitation that are implemented and evaluated in palliative care. Inclusion criteria: This scoping review will consider all studies that focus on qualified health care professionals working in palliative care who are caring for patients 18 years of age or older, and studies that focus on the concepts of palliative rehabilitation interventions. This scoping review will consider all palliative rehabilitation interventions implemented and evaluated in the context of palliative care. Methods: The search strategy aims to find published and unpublished studies. The databases to be searched will include: CINAHL Complete, PubMed, Scopus, SciELO, Cochrane Central Register of Controlled Trials, and PEDro. The search for unpublished studies will include: DART-Europe, OpenGrey, and RCAAP. Studies published in English, Spanish, and Portuguese, and studies that were carried out between 2009 and 2019 will be considered for inclusion. Retrieved papers will be screened for inclusion by two reviewers. Data will be extracted and presented in tabular form and a narrative summary that aligns with the review's objective. Any disagreements that arise between the reviewers will be resolved through discussion or with a third reviewer.